2023
DOI: 10.1088/1674-1137/ac9371
|View full text |Cite
|
Sign up to set email alerts
|

Flux variations of cosmic ray air showers detected by LHAASO-KM2A during a thunderstorm on June 10, 2021*

Abstract: The Large High Altitude Air Shower Observatory (LHAASO) has three sub-arrays, KM2A, WCDA and WFCTA. The flux variations of cosmic ray air showers were studied by analyzing the KM2A data during the thunderstorm on 10 June 2021. The number of shower events that meet the trigger conditions increases significantly in atmospheric electric fields, with maximum fractional increase of 20%. The variations of trigger rates (increases or decreases) are found to be strongly dependent on the primary zenith angle. The flux … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…In other thunderstorm events, increases of the trigger rate are also observed. Recently, thunderstorm ground enhancements (TGEs) and terrestrial gamma-ray flashes (TGFs) are reported in ground based cosmic-ray experiments [7], while further examination is needed to find exact evidence of these phenomena from the experimental data of KM2A.…”
Section: Pos(icrc2023)472mentioning
confidence: 99%
“…In other thunderstorm events, increases of the trigger rate are also observed. Recently, thunderstorm ground enhancements (TGEs) and terrestrial gamma-ray flashes (TGFs) are reported in ground based cosmic-ray experiments [7], while further examination is needed to find exact evidence of these phenomena from the experimental data of KM2A.…”
Section: Pos(icrc2023)472mentioning
confidence: 99%
“…The strength of the atmospheric electric field depends on the air density (altitude) and can reach 1.5-2 kV/cm at altitudes 3-6 km. Several EAS arrays, including those located in Tibet, already report the 20-30% enhancement of the trigger rate during thunderstorms [13][14][15]. Correspondingly, the EAS particle number with energies above the detector threshold is significantly enhanced.…”
Section: Introductionmentioning
confidence: 98%
“…Correspondingly, the EAS particle number with energies above the detector threshold is significantly enhanced. As a remedy for the shower size artificial enhancement, the shower size was reduced, resulting in changes in the detector trigger rate [15]. At Aragats was registered 400% enhancement of MAKET array trigger rate on 19 September 2019 [2,16].…”
Section: Introductionmentioning
confidence: 99%